A Cu-incorporated polymeric heterogeneous catalyst: exploring an expedient approach to construct amide bonds and extending its application to triazole hybrid amide synthesis. (11th April 2023) - Gajurel, Sushmita; Sarkar, Fillip Kumar; Sarkar, Rajib; Kyndiah, Lenida; Pal, Amarta Kumar
Abstract : This work highlights the applications of polymeric copper complex in the synthesis of amides and triazole containing amides. Abstract : A self-assembled copper-grafted imidazole polymeric complex was synthesized using a coordinative-convolution method. The structural characterization of the polymeric copper catalyst was performed using FT-IR, SEM, TEM-EDX, SAED, PXRD, TGA, RAMAN, XPS, and ICP-OES techniques. Furthermore, its potential application was examined in constructing amide bonds and amide bonds consisting of triazole moieties in an aqueous medium. The high catalytic activity, stability, insolubility, and insensitiveness to undergo recuperation of the synthesized polymeric copper catalyst confirmed the heterogenic nature of the catalyst. This synthetic route embraces suitable reaction conditions, eliminating the issue of prolonged reaction time via a Cu-catalyzed synthesis of amides. Moreover, sustainable synthetic conditions, easy recovery, and reusability are the major advantages of the protocol.